Crowd surrounds the Avro 504K biplane, Australia, ca. 1921 (1921)
Inscription indicates this is the Avro biplane of Australian aircraft designer and pilot Captain Edgar Wikner Percival, but it may be Australian aviator's Lieutenant Frank Leonard Roberts aeroplane according to reference sources.
Title devised by cataloguer based on inscription and reference sources.
Part of collection: E.A. Crome collection of photographs on aviation.
Inscription: "Edgar Percival, Murwillumbah"--On reverse.
Also available online
National Library of Australia Manuscript collection MS 1925.
Keywords: Percival, Edgar, -- 1897-1984 -- History; Roberts, Frank, -- 1896-1993 -- History; Avro 504 (Military aircraft) -- Photographs; Aeronautics -- Flights -- Photographs; Aeronautics -- Australia -- Photographs; Australia -- Photographs